The introduction of coinage in Europe did not change pre-existing monetary patterns - Ialongo, Nicola (Frontiers in Human Dynamics, 2024)
IntroductionThis paper investigates whether the introduction of coinage in Europe fundamentally changed pre-existing monetary circulation patterns. By analysing the statistical properties of bronze money before and after the advent of coinage (c. 1500–27 BCE), it challenges the prevailing assumption that coinage revolutionized the use and exchange of money. The research engages with longstanding academic debates between competing theories, which posit that money is either market-driven or state-imposed.MethodsUsing a combination of archaeological data and quantitative analysis, the study examines large datasets of pre-coinage money and early coinage, focusing on weight-based regulation and the log-normal distribution of mass values as key indicators of monetary behaviour.ResultsThe findings reveal that pre-coinage bronze money, consisting of weighed metal fragments, circulated in a manner similar to early coinage. Both forms of money complied with weight-based systems and exhibited log-normal distribution patterns, reflecting structured economic behaviours. The analysis suggests that the introduction of coinage did not lead to a fundamental transformation in how money circulated but rather continued pre-existing patterns.DiscussionThese results challenge the assumption that state-issued coinage marked a watershed moment in the history of monetary economies. The paper proposes that the beginning of coinage introduced a minor technological improvement rather than a revolutionary change in monetary circulation, offering a new perspective on the continuity between pre-coinage and coinage-based economies in ancient Europe.